Levels of Enzymes Involved in Polyamine Synthesis in Patients with Pulmonary Hypertension (Bangladesh Journal of Medical Science, 2026)
Background Pulmonary hypertension (PH) is a multifactorial disease characterized by elevated pulmonary artery pressure and progressive vascular remodeling. Polyamines are implicated in cell proliferation and vascular pathology. While elevated polyamine levels have been observed in PH, the expression of key enzymes involved in their biosynthesis ornithine decarboxylase (ODC), arginine decarboxylase (ADC), and agmatinase (AGMAT) has not been thoroughly examined across PH subtypes. Methods This cross-sectional study included 78 individuals: 21 controls and 57 PH patients categorized into Group 1 (PAH), Group 2 (PH due to left heart disease), and Group 3 (PH due to lung diseases or hypoxia). PH diagnosis was based on current ESC/ ERS guidelines. Serum levels of ODC, ADC, and AGMAT were measured using ELISA. Echocardiographic and laboratory parameters were also recorded. Results While intergroup comparisons among PH subtypes did not reveal significant differences in enzyme levels, patients in all PH groups exhibited numerically higher ODC and ADC levels compared to controls. Mean ODC concentrations were 12.8 ± 8.6 ng/ mL in controls and ranged from 17.0 ± 11.8 to 18.4 ± 12.4 ng/ mL in PH groups. Similarly, ADC levels were elevated in PH groups (83.4 ± 53.8 to 87.6 ± 55.8 ng/mL) compared to controls (70.8 ± 26.9 ng/mL). AGMAT levels showed no significant differences. Group 1 PH patients received targeted therapies per current guidelines. Echocardiographic assessments confirmed expected hemodynamic distinctions across groups. Conclusion Our findings suggest a potential upregulation of polyamine biosynthesis in PH, particularly via ODC and ADC pathways. Although not statistically significant, these trends support a metabolic contribution to PH pathophysiology. Further research with larger cohorts’ studies is needed to validate these enzymes as biomarkers or therapeutic targets.BJMS, Vol. 25 No. 02 April’26 Page: 487-495